Determinants that Influence Students Knowledge about Introduction to Midwifery Laboratory Equipment - Karimah, Rohmatun; Arica, Arica (Jurnal Ners, 2023)
The background to this research is that knowledge regarding laboratory equipment has not yet become an important part of the practicum teaching and learning process. The introduction of tools is usually accompanied by the implementation of laboratory practice so that it will influence students' knowledge of the names, functions, and how to operate the tools. The aim of this research is to analyze the determinants that influence students' knowledge regarding the introduction of laboratory equipment. The research method used is qualitative research. Data was collected using a questionnaire with a cross-sectional approach. The research results showed that the variable of current midwifery education level and the variable of obtaining information from reading sources were significantly related to midwifery students' knowledge. The conclusion obtained is that the level of midwifery education greatly influences students' knowledge because the process of introducing midwifery laboratory equipment is getting better with more and more diverse types of equipment being introduced. Apart from that, reading sources needs to be completely available and easily accessible. So in the future, the introduction of midwifery laboratory equipment must start from the first semester and include the introduction of all laboratory equipment